SOLATION AND CHARACTERIZATION OF A NOVEL BENZOATE- UTILIZING Serratia marcescens - SURYANTO, DWI; SUWANTO, ANTONIUS (BIOTROPIA, 2011)
A new benzoate-utilizing strain, Serratia marcescens DS-8, isolated from the environment was characterized. The strain was enterobacilli, Gram negative, mesophilic, non halophilic, and aerobic bacterium that showed motile ovale- rod shaped cells. The isolate produced extracellular chitinase, protease, and prodigiosin (a red pigment produced by several Serratia strains yielding bright red or pink colonies). A physiological assay using Microbact* test showed that the strain was closely related to Klebsiella ozaenae (49.85%) and Serratia liquefaciens (24.42%), respectively. However, 16S rRNA sequence analysis indicated that the strain was closely related to S. marcescens DSM 30121 with similarity level of 98%. DS-8 strain was able to synthesize its own vitamins. Optimum growth in benzoate was obtained at pH between 7-8.5 and NaCl concentration of 1-1.5% (w/v). The isolate could grow in benzoate-containing medium up to 10 mM. Other carbon sources that could support the growth of DS-8 were casamino acid, glutamate, glucose, acetate, potato starch, and ethanol. Keywords: Serratia marcescens/aromatic degradation/168 rRNA sequence